2001
DOI: 10.1080/030097401750065319
|View full text |Cite
|
Sign up to set email alerts
|

Cancer polyarthritis resembling rheumatoid arthritis as a first sign of hidden neoplasms: Report of two cases and review of the literature

Abstract: Recent onset arthritis reminiscent of rheumatoid arthritis (RA) may be an early manifestation of an occult malignancy. In this report, we present two patients with cancer-associated polyarthritis. Both suffered from symmetric polyarthritis when initially visiting their physicians and did not achieve relief when treated with non-steroidal anti-rheumatic drugs (NSAIDs). In both patients, subsequent work-up led to the diagnosis of an underlying malignancy. One patient suffered from small cell lung cancer (SCLC), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(12 citation statements)
references
References 26 publications
3
9
0
Order By: Relevance
“…Pfitzenmeyer et al [ 58 ] later added the absence of characteristic radiologic lesions to the list of typical features ( Box 1 ). These features have been supported by recent case reviews [ 2 , 3 , 8 , 10 ]. It is now well recognised that rheumatic syndromes often precede the diagnosis of malignant disease [ 1 – 3 , 8 , 57 ].…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…Pfitzenmeyer et al [ 58 ] later added the absence of characteristic radiologic lesions to the list of typical features ( Box 1 ). These features have been supported by recent case reviews [ 2 , 3 , 8 , 10 ]. It is now well recognised that rheumatic syndromes often precede the diagnosis of malignant disease [ 1 – 3 , 8 , 57 ].…”
Section: Discussionsupporting
confidence: 66%
“…These features have been supported by recent case reviews [ 2 , 3 , 8 , 10 ]. It is now well recognised that rheumatic syndromes often precede the diagnosis of malignant disease [ 1 – 3 , 8 , 57 ]. Racanelli et al found that, in patients with solid tumours, only 11.5% had a malignancy diagnosed at the time of their rheumatic presentation, while 88.5% were diagnosed after their initial presentation [ 59 ].…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations